Isotropic and Anisotropic P Wave Velocity Structures of the Crust and Uppermost Mantle Beneath Turkey. Issue 12 (28th November 2020) - Wang, Haibo; Huang, Zhouchuan; Eken, Tuna; Keleş, Derya; Kaya‐Eken, Tulay; Confal, Judith M.; Erman, Ceyhun; Yolsal‐Çevikbilen, Seda; Zhao, Dapeng; Taymaz, Tuncay
Abstract: Compressional and extensional tectonics following northward plate convergences since the Miocene have formed the major surface features in Turkey, such as faulting and orogeny. Despite increasing efforts in last few decades aiming to elucidate the current architecture of the crust and mantle beneath Turkey, several issues regarding the depth extent of the deformation zones, crust‐mantle interaction (e.g., coupling and decoupling) in relation to the deformation, and stress transmission in the lithosphere remain elusive. Here we present high‐resolution 3‐D P wave isotropic and azimuthal anisotropic velocity models of the crust and uppermost mantle beneath Turkey by inverting 204, 531 P wave arrival times of 8, 103 local crustal earthquakes. Our results reveal low‐velocity anomalies or velocity contrasts down to the uppermost mantle along the North and East Anatolian Fault Zones. The fast velocity directions (FVDs) of azimuthal anisotropy in the lower crust and uppermost mantle are parallel to the regional maximum extensional directions in western Turkey, and the FVDs in the crust and uppermost mantle are parallel to the surface structures in southeastern Turkey. These results indicate that vertically coherent deformation between the crust and uppermost mantle occurs in western and southeastern Turkey. However, in central northern Turkey, the FVDs in the uppermost mantle are oblique to both the FVDs in the lower crust and the maximum shear directions derived from GPS measurements, suggesting that the crust and lithospheric mantle are decoupled there. Key Points: High‐resolution models of isotropic and azimuthal anisotropic P wave velocity beneath Turkey are determined Vertically coherent deformation between the crust and lithospheric mantle occurs in western and southeastern Turkey The crust and upper mantle are decoupled in central northern Turkey